Characterization and structural analysis of a versatile aromatic prenyltransferase for imidazole-containing diketopiperazines - Wenxue Wang; Peng Wang; Chuanteng Ma; Kang Li; Zian Wang; Yuting Liu; Lu Wang; Guojian Zhang; Qian Che; Tianjiao Zhu; Yuzhong Zhang; Dehai Li (Nature Communications)
Abstract Prenylation modifications of natural products play essential roles in chemical diversity and bioactivities, but imidazole modification prenyltransferases are not well investigated. Here, we discover a dimethylallyl tryptophan synthase family prenyltransferase, AuraA, that catalyzes the rare dimethylallylation on the imidazole moiety in the biosynthesis of aurantiamine. Biochemical assays validate that AuraA could accept both cyclo-(L-Val-L-His) and cyclo-(L-Val-DH-His) as substrates, while the prenylation modes are completely different, yielding C2-regular and C5-reverse products, respectively. Cryo-electron microscopy analysis of AuraA and its two ternary complex structures reveal two distinct modes for receptor binding, demonstrating a tolerance for altered orientations of highly similar receptors. The mutation experiments further demonstrate the promiscuity of AuraA towards imidazole-C-dimethylallylation. In this work, we also characterize a case of AuraA mutant-catalyzed dimethylallylation of imidazole moiety, offering available structural insights into the utilization and engineering of dimethylallyl tryptophan synthase family prenyltransferases.